a)85.(35-27)-35.(85-27)
=85.35-27-35.85-27
=(85-85).(35-35).(27-27)
=0.0.0
=0
b)47.(45-15)-47.(45+15)
=47.45-15-47.45+15
=(47-47).(45-45).(15+15)
=0.0.30
=0
a) 85 . ( 35 - 27 ) - 35 . ( 85 - 27 )
= 85 . 35 - 85 . 27 - 35 . 85 + 35 . 27
= ( 85 . 35 - 35 . 85 ) - 27 . ( 85 - 35 )
= 0 - 27 . 50
= 0 - 1350
= -1350
b) 47 . ( 45 - 15 ) - 47 . ( 45 + 15 )
= 47 . ( 45 - 15 - 45 - 15 )
= 47 . (-30)
= -1410
Học tốt !!!
=))
a) 85 . ( 35 - 27 ) - 35 . ( 85 - 27 )
= 85 . 35 - 85 . 27 - 35 . 85 - 35 . 27
= ( 85. 35 - 35 . 85 ) - 27 . ( 85 - 35 )
= 0 - 27 . 50
= 0 - 1350
= -1350
Vậy : 85.(35-27) - 35.(85-27) = -1350
b) 47 . ( 45 - 15 ) - 47 . ( 45 + 15 )
= 47 . ( 45 - 15 - 45 - 15 )
= 47 . ( - 30 )
= -1410
Vậy : 47.(45-15) - 47.(45+15) = -1410